Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1214/ejp.v19-3742
|View full text |Cite
|
Sign up to set email alerts
|

From sine kernel to Poisson statistics

Abstract: We study the Sine β process introduced in [B. Valkó and B. Virág. Invent. math. 177 463-508 (2009)] when the inverse temperature β tends to 0. This point process has been shown to be the scaling limit of the eigenvalues point process in the bulk of β-ensembles and its law is characterized in terms of the winding numbers of the Brownian carrousel at different angular speeds. After a careful analysis of this family of coupled diffusion processes, we prove that the Sine β point process converges weakly to a Pois… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 22 publications
(50 reference statements)
2
35
0
Order By: Relevance
“…In the bulk, the eigenvalues of the β-ensembles converge towards the Sine β process [VV09]. In the small β limit, the Sine β process was also shown to converge towards a (homogeneous) Poisson point process [AD14a] using its characterization via coupled diffusions. Closely related discrete models are Jacobi matrices with random decaying potential [KVV12] and CMV matrices [KS09].…”
Section: Statement Of Our Resultsmentioning
confidence: 99%
“…In the bulk, the eigenvalues of the β-ensembles converge towards the Sine β process [VV09]. In the small β limit, the Sine β process was also shown to converge towards a (homogeneous) Poisson point process [AD14a] using its characterization via coupled diffusions. Closely related discrete models are Jacobi matrices with random decaying potential [KVV12] and CMV matrices [KS09].…”
Section: Statement Of Our Resultsmentioning
confidence: 99%
“…Allez-Dumaz [1] showed that Sine β d → P oisson(dλ/2π) as β → 0. This fact can easily be generalized to other processes where the drift term in the corresponding SDE (1.3) is replaced by functions f with mild conditions [12].…”
Section: Introductionmentioning
confidence: 99%
“…so that, by setting β = n − 1 γ , we can use the idea of [1] : to study the hitting time of Θ nt (λ) to the set πZ, we consider…”
Section: Introductionmentioning
confidence: 99%
“…For real-symmetric ensembles, the same question has recently been considered from a formal point of view. Indeed, in [4,5], Allez and Dumaz considered the β → 0 limit of the Sine-β process and of the β-Tracy-Widom distribution. The β → 0 limit of the Sine-β is also considered by Leblé and Sefaty in [19].…”
Section: Introductionmentioning
confidence: 99%
“…The β → 0 limit of the Sine-β is also considered by Leblé and Sefaty in [19]. The approach used by [19] is based on approximation theory while [4] use the diffusion representation of the Sine-β process to consider the limit β → 0. One would expect again to prove that when β → 0 simultaneously to N → ∞, the eigenvalues in the vicinity of a point u in the bulk of the spectrum exhibit Poisson statistics.…”
Section: Introductionmentioning
confidence: 99%